2016
DOI: 10.1097/mpg.0000000000001000
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intake, Energy Expenditure, and Growth of Infants Following Congenital Diaphragmatic Hernia Repair

Abstract: Optimal weight gain can be achieved with higher than predicted calorie provision. Most infants with CDH are hypermetabolic. Despite this, failure to thrive prevalence can improve during the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
5
42
0
Order By: Relevance
“…In the higher EN2w group there was better weight gain than in the lower EN2w group; this is consistent with previous reports . Bairdain et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the higher EN2w group there was better weight gain than in the lower EN2w group; this is consistent with previous reports . Bairdain et al .…”
Section: Discussionsupporting
confidence: 90%
“…reported that the measured resting energy expenditure in CDH patients was higher than the predicted resting energy expenditure. Furthermore, a caloric intake of 125 kcal/kg/day at discharge from hospital was required to achieve an adequate weight gain . Considering that patients with increased respiratory effort have increased caloric demands, the amount of EN should be increased until an adequate bodyweight gain can be ensured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that children with recurrent hospitalisations more often received dietary interventions. Close involvement of multidisciplinary nutrition support teams was indeed found to prevent failure to thrive in patients with congenital diaphragmatic hernia 36. It is worth recommending to have such teams, including dietitians and speech-language pathologists, available to support hospitalised children in general, and continue supporting high-risk patients after discharge to home.…”
Section: Discussionmentioning
confidence: 99%
“…found that CDH neonates had an elevated resting energy expenditure as measured by indirect calorimetry, and these neonates expended 30% more calories than expected to meet the required weight gain. The hypermetabolic state of CDH neonates was attributed to increased energy requirements for growth due to increased respiratory effort secondary to lung hypoplasia . Mehta et al .…”
Section: Discussionmentioning
confidence: 99%